Tuberculosis of the Spermatic Cord: Case Report - Amine Benjelloun; Abderrahim Elktaibi; Younes Elharrech; Driss Touiti; Omar Ghoundale (Urology Case Reports, 2014)
The spermatic cord tuberculoma is uncommon, especially in its lower portion. Most cases were described in Japanese literature. We report a case of tuberculosis of the spermatic cord in a sexually active young man, revealed by a scrotal mass mimicking a tumor of the testicle and discuss the suitable diagnostic and therapeutic procedures, with preservation of the testes and the other sexual organs.